2015
DOI: 10.12693/aphyspola.127.204
|View full text |Cite
|
Sign up to set email alerts
|

Electron Phase Separations Involving Superconductivity in the Extended Hubbard Models with Pair Hopping Interaction

Abstract: In this work the extended Hubbard models with pair hopping interaction (at the atomic limit) are investigated within the variational approach, which treats the on-site interaction term exactly and the intersite interactions within the mean-eld approximation (exact in d → +∞). We analyze mutual stability of the superconducting phase and charge or (ferro/antiferro-)magnetic orderings as well as homogeneous mixed phases. Our preliminary results for U = 0 show that the superconducting phase can coexist with the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Let us stress that it has been reported that superconductivity can coexist with charge-ordered and magnetically ordered phases in states with phase separations [32,36,37,67,68]. In present work we do not consider the charge and magnetic orderings.…”
Section: Conclusion and Supplementary Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Let us stress that it has been reported that superconductivity can coexist with charge-ordered and magnetically ordered phases in states with phase separations [32,36,37,67,68]. In present work we do not consider the charge and magnetic orderings.…”
Section: Conclusion and Supplementary Discussionmentioning
confidence: 93%
“…The pair-hopping term (J) was first proposed in Refs. [29 and 30] by Penson and Kolb in 1986 and it can be derived from a general microscopic tight-binding Hamiltonian, where the Coulomb repulsion may lead to the pair hopping interaction J = ii|e 2 /r|jj [17][18][19][20][21][22][23][32][33][34][35][36][37][38]. In such a case J is positive (repulsive model J > 0, favoring η-wave SC), but in this case the magnitude of J is very small.…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This interplay can lead to either mutual enhancement or reduction of mentioned phenomena, e.g. [10][11][12][13][14][15]20]. Moreover, various types of charge-order exist in superconducting and multiferroic materials.…”
Section: Introductionmentioning
confidence: 99%